1988
DOI: 10.1530/jrf.0.0830825
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal fluctuations in plasma progesterone concentrations in Gentile-di-Puglia and Ile-de-France ewes in southern Italy

Abstract: Summary. Ile-de-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It can be said that 36.4% of ewes show estrous regularly throughout the year. These results showed that WK has a comparatively long breeding season when compared with other northern hemisphere sheep breeds (Bartlewski et al, 1999a;Dell'Aquila et al, 1988;Gómez-Brunet et al, 2008). The results from our anestrous P4 levels were also similar with anestrous P4 levels from other sheep breed (Ferreira-Silva et al, 2017;Sasa, Rodrigues, Nonaka, Balieiro, & Coelho, 2016).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It can be said that 36.4% of ewes show estrous regularly throughout the year. These results showed that WK has a comparatively long breeding season when compared with other northern hemisphere sheep breeds (Bartlewski et al, 1999a;Dell'Aquila et al, 1988;Gómez-Brunet et al, 2008). The results from our anestrous P4 levels were also similar with anestrous P4 levels from other sheep breed (Ferreira-Silva et al, 2017;Sasa, Rodrigues, Nonaka, Balieiro, & Coelho, 2016).…”
Section: Discussionmentioning
confidence: 81%
“…Breeding season lengths according to endocrinological and behavioral data in WK were found noticeably longer than breeding season lengths for Ile de France and Gentile de Puglia breeds (Dell'Aquila, Varriale, & Alberico, 1988). White Karaman breeding season lengths from behavioral data were also longer than some Turkish sheep breed such as Dağlıç and Chios (Kaymakçı, 1984;Kaymakçı et al, 1987).…”
Section: Discussionmentioning
confidence: 87%